2022
DOI: 10.1016/j.breast.2021.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Are English-language online patient education materials related to breast cancer risk assessment understandable, readable, and actionable?

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
4

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
(44 reference statements)
1
9
0
4
Order By: Relevance
“…This systematic assessment of breast density websites from English-speaking countries found that information given to women varied in terms of content, readability, understandability and actionability. Similar to recent findings on breast cancer risk assessment information online and previous findings on readability and understandability of various sources of breast density information, readability was overall high meaning that it was well above the international recommended grade 6–8 reading level [ 26 , 27 , 31 , 32 ], and understandability was poor amongst a large sample of the websites [ [15] , [16] , [17] , [18] , 32 ]. However, all earlier breast density studies only assessed US-based information and did not comprehensively assess (e.g.…”
Section: Discussionsupporting
confidence: 83%
“…This systematic assessment of breast density websites from English-speaking countries found that information given to women varied in terms of content, readability, understandability and actionability. Similar to recent findings on breast cancer risk assessment information online and previous findings on readability and understandability of various sources of breast density information, readability was overall high meaning that it was well above the international recommended grade 6–8 reading level [ 26 , 27 , 31 , 32 ], and understandability was poor amongst a large sample of the websites [ [15] , [16] , [17] , [18] , 32 ]. However, all earlier breast density studies only assessed US-based information and did not comprehensively assess (e.g.…”
Section: Discussionsupporting
confidence: 83%
“…K. Patel et al, 2015;Vishnevetsky et al, 2018). This criterion was evaluated in 23 studies (Abdul Rahman et al, 2020;Alshehri & Joury, 2019;Alwani et al, 2021;Arslan et al, 2020;Bacher et al, 2020;Balakrishnan, Chandy, Hseih, et al, 2016;Bui et al, 2018;Edmunds et al, 2014;Georgsson & Carlsson, 2022;Gillum, 2017;Guitton, 2015;Gulbrandsen et al, 2022;Harris et al, 2018;Hughes et al, 2019;Lake et al, 2007;Lamb et al, 2022;Lipari et al, 2019;Mac et al, 2020;Magrath et al, 2022;Mani et al, 2021;McClure et al, 2016;Miles et al, 2021;O'Sullivan et al, 2020;Sideris et al, 2021;Townsend, 2011;Unaka et al, 2017;van Ballegooie & Hoang, 2021;Vishnevetsky et al, 2018;Wang et al, 2022).…”
Section: Comprehensibility or Comprehensionunclassified
“…(Continues) Bui et al, 2018;Gillum, 2017;Guitton, 2015;Gulbrandsen et al, 2022;Harris et al, 2018;Lamb et al, 2022;Lipari et al, 2019;Magrath et al, 2022;McClure et al, 2016;Miles et al, 2021;Sideris et al, 2021;Vishnevetsky et al, 2018;Wang et al, 2022).…”
Section: Formattingunclassified
“…According to Bojovi et al [37], online education must be built on a unique technological, social and economic context, which may not offer teachers enough time to change the original teaching plans, thereby reducing the efficiency of online education [38][39][40]. During COVID-19, a considerable amount of research on online education was presented; however, the majority was focused on certain professional fields, such as health care [4,5] and teacher education [6][7][8][9]. The influence of online courseware on users' willingness to engage in online classes, which is taken as an essential technical instrument for online education, on the other hand, has received less attention.…”
Section: Literature 21 Current Status Of Online Education Developmentmentioning
confidence: 99%
“…As a result, it is critical to identify the elements that impact users' use of online classroom APPs. Although there have been a large number of studies on online education and online classroom APPs since the outbreak of the COVID-19, the majority of the relevant studies have been focused on specific professional disciplines, such as medical care [4,5] and teacher education [6][7][8][9], while studies on online class APPs have primarily been focused on the features of software itself, such as usability [10][11][12] and interface design [13], leaving the lack of a systematic and comprehensive discussion on the factors influencing users' use of online classroom APPs.…”
Section: Introductionmentioning
confidence: 99%